Spatial and temporal distribution of Anopheles mosquito's larvae and its determinants in two urban sites in Tanzania with different malaria transmission levels - Mathania, Mary Mathew (Parasite Epidemiol Control, 2020)
BACKGROUND: In order to be able to design and implement control measures directed to the mosquito larva stages an understanding of the spatial and temporal distribution and its determinants in different malaria transmission settings is important. This study therefore, intended to determine the spatial and temporal distribution of Anopheles mosquito's larvae and its determinants in two urban sites with different transmission levels, in Tanzania. METHODOLOGY: This study was conducted in Dodoma and Morogoro regions in Tanzania. The study was an ecological study of repeated cross-sectional type. Searching for water bodies in the selected wards was done by going around all streets. Potential breeding sites were given unique identification numbers and larval sampling was done using the standard dipping method with a 350 ml mosquito scoop and a calibrated pipette. Visual identification of presence of larvae and its abundance in each sampling were used to describe the larvae density. A sample of Anopheles mosquitoes which emerged from collected larvae, were processed for species identification using PCR. Descriptive statistics were arrived at by calculating different proportions for the variables. The overall impact of the variables on the density of Anopheles larvae was tested using multiple logistic regression. Variables with p-value less than 0.05 were regarded as significant. RESULTS: A total of 724 water bodies out of which, 576 (79.6%) potential breeding sites were analyzed. It was found that, most (96.2%) of the potential breeding sites were manmade and most (59.5%) were less than 5 m in diameter and 87.2% were within 100 m from human settlement. Out of all the potential breeding sites, 69.8% and 30.2% were in Morogoro and Dodoma respectively, out of which 72.2% and 68.4% respectively, were found during rainy season. Habitats with clean water, at a distance of 10–100 m from the house, in natural, shaded and partial sunlight habitats had higher odds of having high density of mosquito larvae than their counterparts (p < .05). The PCR analysis showed that 72.5% were An. arabiensis, 4.5% An. gambiaes.s, 0.5% An.coustaniand 20% An. quadrianulatuswhile 2.5% of the samples could not be identified because DNA was not amplified. CONCLUSION AND RECOMMENDATION: Type of water, distance from the breeding site to human settlement, light intensity and habitat origin were significant predictors of variation on the spatial and temporal distribution of Anopheles mosquito breeding sites. With increased global emphasis on control measures that targets mosquito immature stages; we recommend that larval control measures should be developed while considering the findings from this study.